Bullying Perpetration: The Role of Child Abuse and Self-Esteem among Secondary School Students in Ile-Ife - Abayomi O. Olusa; Oluwafisayomi A. Owotade (Richtmann Publishing, 2022)
The purpose of this study was to examine the influence of child abuse and self-esteem on bullying perpetration among secondary school students in Ile-Ife, Osun State. A multi-stage sampling technique was used to select 324 participants. They responded to the child abuse questionnaire, the Rosenberg self-esteem scale and the Adolescent Peer Relations Instrument. Findings revealed that self-esteem did not predict the three forms of bullying. The experience of physical and emotional childhood abuse predicted verbal, social and physical bullying, while sexual childhood abuse predicted social and physical bullying. Based on these results, it was recommended that parents should be conscious of corporal punishment and other activities that could lead or reflect as abuse and neglect on their children. Received: 21 June 2022 / Accepted: 26 August 2022 / Published: 2 September 2022